THE FEMINIST AGENDA, A FALL OF HIERARCHAL REDRESS OR AN ATTEMPT TO ESTABLISHING AN ‘EQUAL’ SOCIETY GONE WRONG: AN INTERNAL CRITIQUE TO FEMINIST THEORIES* (The Pretoria Student Law Review, 2021)
The aim of this paper is to interrogate the post-1994 feminist approaches to jurisprudential discourse. This interrogation will include a consideration as to whether critical instead of ‘traditional’ feminist theories contribute in transforming or decolonising South African law and jurisprudence. It is my suggestion that the inquiry to address ‘gender equality’ before and without addressing issues of racism and racial classism simultaneously in South Africa contributes effectively to the continued marginalisation of black women. As such, my position attempts to engage with the critical feminist approaches in order to address the prejudices that traditional feminist approaches impose on black women. The focal theoretical point of departure for this interrogation is critical race feminism.2 Critical race feminism proposes a progressive initiative for addressing the inconsistencies embodied within the traditional feminist approaches and is thus suitable for the South African post-apartheid context as it may trigger ‘transformative possibilities’.3 It is my contention that in order to address the marginalisation of black women, the traditional feminist approaches (such as the dominant feminist approaches) must be done away with for they are a hindrance to legal reform, as they prejudice the very structure they claim to protect.
Keywords: feminist approaches; jurisprudential discourse; South African law; marginalisation of black women; legal reform